Atenção visual e congruência de embalagem em ambiente de laboratório de varejo com o uso de eye tracking - Gallina, Mariângela (2018)
Research on visual attention and consumer behavior reports how packaging design raises interest and stimulates point of sale choice. However, little attention is dedicate to packaging, that has a similar layout or congruent. The empiricist of this dissertation evaluates the decision making of the consumer in front of a packaging with congruent layout between the brands of the same category of product. It divided into three studies, all performed in a retail laboratory environment and using eye tracking. Two studies were exploratory, being that the second was the inclusion of a controlled variable, the observation distance. The third was an experiment with hypothesis testing constructed from the previous results and supported in the literature review. The results of the study show a correspondence between the shelf position and consumer choice, regardless of the congruent factors and distance of observation. The inputs serve as a basis for future research, can be validated for other product categories, and subsidize marketing strategies and packaging design.